Blocking and Destroying Food Aid in Conflict Areas According to International Law - Umarella, Andriani Putri Sari; Tahamata, Lucia Charlota Octavina; Daties, Dyah Ridhul Airin (Fakultas Hukum Universitas Pattimura, 2025)
Introduction: The ongoing Israeli conflict in Gaza has triggered a severe food crisis due to the blocking and destruction of food aid, violating IHL provisions that prohibit starvation as a warfare tactic and attacks on objects essential for civilian survival.Purposes of the Research: This research examines IHL regulations and legal measures concerning food aid in the Gaza conflict.Methods of the Research: The study employs normative legal research by analyzing legal library materials through legislative, case-based, and conceptual approaches. The sources of legal materials include primary, secondary, and tertiary materials, collected through library research and analyzed qualitatively.Results of the Research: The findings indicate that IHL safeguards humanitarian aid, including food, in conflict zones, as outlined in the 1949 Geneva Conventions and the 1977 Additional Protocol I. Article 23 of the Fourth Geneva Convention mandates that warring parties permit humanitarian aid delivery, while Article 54 of Additional Protocol I prohibits destroying objects vital for civilian survival. Blocking and destroying food aid constitutes a grave breach, classified as a war crime under the 1998 Rome Statute. Legal enforcement mechanisms include decisions by the International Court of Justice (ICJ), investigations by the International Criminal Court (ICC), UN Human Rights Council (UNHRC) fact-finding missions, and humanitarian organizations such as the International Committee of the Red Cross (ICRC).